Integrating HIV, hepatitis B and syphilis screening and treatment through the Maternal, Newborn and Child Health platform to reach global elimination targets - Joseph Woodring; Naoko Ishikawa; Mari Naga; Maya Malarski; Yoshihiro Takashima; Howard Sobel; Ying-Ru Lo (World Health Organization Regional Office for the Western Pacific, 2017)
Every year, an estimated 180 000 babies in the Western Pacific Region are infected by hepatitis B, 13 000 by syphilis and 1400 by HIV through mother-to-child transmission.1 These infections can be largely prevented by antenatal screening, treatment and timely vaccination for newborns. Despite challenges in controlling each disease, major achievements have been made. National immunization programmes have reduced the regional hepatitis B prevalence from over 8% in 1990 to 0.93% among children born in 2012. In addition, HIV testing and treatment have helped keep the regional prevalence of HIV infections at 0.1%. In contrast, the number of maternal syphilis cases is still high in the Western Pacific Region, with an estimated 45 million cases in 2012. Elimination of mother-to-child transmission of these infections cannot be achieved through vertically applied programming and require using and augmenting to the shared Maternal, Newborn and Child Health platform to coordinate, integrate and enable cost efficiencies for these elimination efforts. The Regional Framework for Triple Elimination of Mother-to-Child Transmission of HIV, Hepatitis B and Syphilis in Asia and the Pacific 2018-2030 offers such a coordinated approach towards achieving the triple elimination of mother-to-child transmission of HIV, hepatitis B and syphilis and provides guidance for decision-makers, managers and health professionals working in programmes addressing maternal, newborn and child health, HIV, hepatitis, sexually transmitted infections and immunization.